ROLE AND ECONOMIC POLICIES AND POLICIES DEPARTMENT OFTOURISM AND CREATIVE ECONOMY DEVELOPMENT DISTRICT BELITUNGCape Kelayang TOURISM DESTINATION AS ICON AND ENDS SPEARTOURISM BELITUNG - Trihaji, Edit; Priyanto, Priyanto (Journal of Indonesian Tourism and Policy Studies, 2018)
The Focus in this study is to discuss the development of tourism, particularly conducted by the Department of Ceative Economy and Tourism Belitung Regency in the development of tourism destination Tanjung Kelayang as icon and the spearhead of tourism Belitung as alternative tourist destinations. Tourism is important to the district of Belitung, for being the third largest source of foreign exchange, the wealth of natural and cultural potential of a very broad and diverse, besides tourism an effective tool in empowering and improving the local economy. The authors found significant value that can be taken from the Tourism Village development within the framework of community development is to increase the consumption of local products, empowering the local work force, for example tour guides, lodge manager (homestay), restaurants, craftsmen, performing arts, Increase public awareness of the values traditions and local culture and the uniqueness of its natural environment. The results also revealed a tourist village development initiatives generated by society and government encouragement, needs to be integrated with the global tourism associated with marketing by (travel agent / tour operator) in order to have access to the tourist market